Root-Associated Fungal Communities From Two Phenologically Contrasting Silver Fir (Abies alba Mill.) Groups of Trees - Tina Unuk; Tijana Martinović; Tijana Martinović; Domen Finžgar; Nataša Šibanc; Nataša Šibanc; Tine Grebenc; Hojka Kraigher (Frontiers in Plant Science, 2019)
Root-associated fungal communities are important components in ecosystem processes, impacting plant growth and vigor by influencing the quality, direction, and flow of nutrients and water between plants and fungi. Linkages of plant phenological characteristics with belowground root-associated fungal communities have rarely been investigated, and thus our aim was to search for an interplay between contrasting phenology of host ectomycorrhizal trees from the same location and root-associated fungal communities (ectomycorrhizal, endophytic, saprotrophic and pathogenic root-associated fungi) in young and in adult silver fir trees. The study was performed in a managed silver fir forest site. Twenty-four soil samples collected under two phenologically contrasting silver fir groups were analyzed for differences in root-associated fungal communities using Illumina sequencing of a total root-associated fungal community. Significant differences in beta diversity and in mean alpha diversity were confirmed for overall community of ectomycorrhizal root-associated fungi, whereas for ecologically different non-ectomycorrhizal root-associated fungal communities the differences were significant only for beta diversity and not for mean alpha diversity. At genus level root-associated fungal communities differed significantly between early and late flushing young and adult silver fir trees. We discuss the interactions through which the phenology of host plants either drives or is driven by the root-associated fungal communities in conditions of a sustainably co-naturally managed silver fir forest.